Retention proposal in complex cavities. - Pedro Alvarez Rodríguez; Eduardo M. Curbeira Hernández; Eduardo Duarte Marrero; Yisell Peláez Rivas; Aracelis Navarro Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
Background: Dental Operatory is the main structure in which Odontology lies. It is not an easy discipline that gives enjoyable results with little effort due to the difficulties that a correct reconstruction of a destroyed dental element offers.The frequency with which pulpar injury occurs while anchoring additional retainers in complex cavities, the technical difficulties the lack of these devices cause and the need to simplify dental procedures lead this study to show the advantages to substitute additional retainers for a retainer surcus. Method: An observational descriptive study was applied to 53 patients(42% of the universe ), sample which was selected by means of a simple randomized sample . From a proximal-occlusal cavity, the preparations were extended in a box-like shape towards the bucal or lingual region and the additional retainers were substituted for a surcus which was performed in the gingival wall of the preparation. Calcium Hydroxide of rapid dryness was used as a cavity cover and Policarboxilate cement as a base; then the amalgam restoration was performed. The number of restorations were studied taking into account the patient´s age and the failures due to fractures of amalgam, loss of vitality and periapical changes were assessed taking into consideration the patient´s age and a one- year follow up. Results: Most of the amalgam restorations were performed in patients aged from 35 to 59 years and the relative frequencies due to fractures of amalgam, loss of vitality and periapical changes were very low. Conclusion: The substitution of additional retainers for a retainer surcus in complex cavities of vital molars showed to be advantageous because it guarantees a less degree of pulpar damage and less pulpar damage.